Prevalensi Rinosinusitis Kronik di Poliklinik THT-KL RSUD dr. Doris Sylvanus Kota Palangka Raya Tahun 2023 dan 2024 - Ariska Agustina; Margaretha Yayu Indah Anugerahny; Indria Augustina; Angeline Novia Toemon; Nuch Sabunga (Universitas Muhamadiyah Manado, 2026)
Chronic rhinosinusitis (CRS) is a long-term inflammatory condition affecting the nasal mucosa and paranasal sinuses, which significantly impacts patients’ quality of life due to persistent and recurrent symptoms. Limited epidemiological data regarding CRS are available in Central Kalimantan, particularly at RSUD dr. Doris Sylvanus in Palangka Raya, prompting this study to determine its prevalence and patient distribution characteristics. This research employed a quantitative descriptive design with a cross-sectional approach. Data were collected from medical records of patients diagnosed with CRS in 2023 and 2024. Univariate analysis was conducted, and results were presented in tables and diagrams illustrating frequency distributions by year, gender, age, and main complaints. The findings showed a total of 118 CRS patients, with 53 cases in 2023 and 65 cases in 2024. The prevalence of CRS increased from 4.91% in 2023 to 10.83% in 2024. Based on gender, males accounted for 50.8% (60 patients), while females represented 49.2% (58 patients). The age group most affected was 46–55 years (31%), indicating a predominance among individuals of productive age. Nasal congestion was the most frequent primary complaint, reported by 35% of patients. The study concludes that the prevalence of CRS at RSUD dr. Doris Sylvanus increased notably from 2023 to 2024, with a slightly higher incidence among males in the productive age group. These findings highlight the need for enhanced preventive measures and early diagnosis to manage CRS more effectively in the local population.